Synthesis and structural characterization of bipyridine ligands towards the application in dye-sensitized solar cells - Thu Thuy, Luong Thi; Hien, Nguyen; Thinh, Tran Quang (Vietnam Journal of Chemistry, 2016)
An efficient synthetic route was developed to tailor bipyridine ligands basing on the palladium catalyzed Sonogashira cross-coupling of 4-bromo-2,2’-bipyridine. Structures of the modified bipyridines were elucidated by NMR and X-Ray diffraction analyses. It was shown that the introduced alkynes are co-planar with the bipyridine core, revealing an efficient effect of the substituent on the electronic properties of the ligand. Keywords. DSSC, 2,2’-bipyridine, dye sensitizers, palladium-catalyzed, Sonogashira.